PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA KELAS RENDAH BERORIENTASI MODEL PEMBELAJARAN DISKUSI - Sony Irianto; Sukristanto Sukristanto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2008)
This development was aimed at creating learning device for low level mathematics to increase the students’ participation and achievement through discussion learning model in Class A of the second semester of the Elementary School Teacher Education Department of Muhammadiyah University of Purwokerto of the academic year 2008/2009. The 49 subject takers was divided into 15 groups of 3 to 4 people. The procedure of developing the device used classroom action research. The action consisted of two cycles and took three months. Each cycle was done depending on the obtained improvement, design and the factor to be developed. The instrument which was used to get the data of participation and students’ response towards the lecture and the learning device was questioner, while he instrument to get data on students learning achievement were essay quiz, mid term test, and the end term test. The result was the device for learning low level mathematics, early-class learning material, students work, and increased learning participation. The learning achievement was still low which was due to their low ability in solving mathematical problem. Key words: Discussion learning model, participation, and mathematics learning achievement.